1993
DOI: 10.1038/365352a0
|View full text |Cite
|
Sign up to set email alerts
|

The T-cell transcription factor NFATp is a substrate for calcineurin and interacts with Fos and Jun

Abstract: Transcription of lymphokine genes in activated T cells is inhibited by the immunosuppressive agents cyclosporin A and FK506, which act by blocking the phosphatase activity of calcineurin. NFAT, a DNA-binding protein required for interleukin-2 gene transcription, is a potential target for calcineurin, cyclosporin A and FK506. NFAT contains a subunit (NFATp) which is present in unstimulated T cells and which forms a complex with Fos and Jun proteins in the nucleus of activated T cells. Here we report that NFATp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
514
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 728 publications
(536 citation statements)
references
References 28 publications
17
514
0
1
Order By: Relevance
“…Moreover, we had shown that Tpl-2 activates NFAT, a complex transcription factor composed of NFAT and AP1 components, whose activation is obligatory for IL-2 induction (Jain et al, 1992;Luo et al, 1996;Northrop et al, 1993;Rooney et al, 1995). Since Tpl-2 activates NFAT as well as the MAPK pathway (Ceci et al, 1997;Tsatsanis et al, 1998), which is required for the activation of AP1 (Jain et al, 1993), we examined whether dominant negative mutants of several proteins transducing signals along these pathways inhibit the activation of the IL-2 promoter by Tpl-2. To this end, EL4 cells were cotransfected with an IL-2 promoter/ CAT reporter construct, a Tpl-2 expression construct and expression constructs of the dominant negative (DN) mutants Ha-ras N17, MEK1S218/222A, Raf1S621A and NFATcD418.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we had shown that Tpl-2 activates NFAT, a complex transcription factor composed of NFAT and AP1 components, whose activation is obligatory for IL-2 induction (Jain et al, 1992;Luo et al, 1996;Northrop et al, 1993;Rooney et al, 1995). Since Tpl-2 activates NFAT as well as the MAPK pathway (Ceci et al, 1997;Tsatsanis et al, 1998), which is required for the activation of AP1 (Jain et al, 1993), we examined whether dominant negative mutants of several proteins transducing signals along these pathways inhibit the activation of the IL-2 promoter by Tpl-2. To this end, EL4 cells were cotransfected with an IL-2 promoter/ CAT reporter construct, a Tpl-2 expression construct and expression constructs of the dominant negative (DN) mutants Ha-ras N17, MEK1S218/222A, Raf1S621A and NFATcD418.…”
Section: Resultsmentioning
confidence: 99%
“…NFAT is a complex factor composed of AP1 and NFAT components (Jain et al, 1993;Northrop et al, 1993). The NFAT component is heterogeneous and is represented by at least four protein isoforms encoded by di erent genes that are di erentially expressed in a variety of cell types.…”
Section: Introductionmentioning
confidence: 99%
“…cJun interacts with the NF-kB subunit p65 to enhance binding to kB and AP-1 sites (Stein et al, 1993). Jun dimers and Jun/Fos heterodimers also form complexes with the T-cell transcription factor NFAT (Jain et al, 1993). The AP-1 and ATF/CREB transcription factors can form selective cross-family heterodimers with distinct DNA binding speciÂźcities.…”
mentioning
confidence: 99%
“…These AP-1 factors can bind to the TRE (TPA-response element) sequence (Angel et al, 1987) and enhance gene expression. AP-1 factors also interact with other transcription factors including NF-kB (Stein et al, 1993), NF-AT (Jain et al, 1993) and glucocorticoid receptor (Jonat et al, 1990;Schule et al, 1990) to regulate gene expression.…”
mentioning
confidence: 99%